2013
DOI: 10.1182/blood-2012-08-449819
|View full text |Cite
|
Sign up to set email alerts
|

VCAM-1 and VAP-1 recruit myeloid cells that promote pulmonary metastasis in mice

Abstract: Key Points• Metastatic tumor cell attachment induces endothelial VCAM-1 and VAP-1.• VCAM-1 and VAP-1 promote metastatic tumor cell survival by recruiting myeloid cells, pointing to VAP-1 as a therapeutic target.Pulmonary metastasis is a frequent cause of poor outcome in cancer patients. The formation of pulmonary metastasis is greatly facilitated by recruitment of myeloid cells, which are crucial for tumor cell survival and extravasation. During inflammation, homing of myeloid cells is mediated by endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 42 publications
1
70
0
Order By: Relevance
“…Macrophage and monocyte populations have been reported to support the seeding of metastatic breast cancer cells in the lung, assisting their extravasation, secreting vascular endothelial growth factor and inducing angiogenesis, and they also promote the growth of metastatic lesions (12,13,41,42,53,54). Macrophages support tumor cell migration and invasiveness by secreting chemotactic epithelial growth factor and matrix-remodeling proteases, such as cathepsins and MMPs (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage and monocyte populations have been reported to support the seeding of metastatic breast cancer cells in the lung, assisting their extravasation, secreting vascular endothelial growth factor and inducing angiogenesis, and they also promote the growth of metastatic lesions (12,13,41,42,53,54). Macrophages support tumor cell migration and invasiveness by secreting chemotactic epithelial growth factor and matrix-remodeling proteases, such as cathepsins and MMPs (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1 was activated by inflammation (8). In addition, it is also expressed in dendritic cells, including macrophages and placental trophoblastic cells, B-lymphocytes, smooth muscle cells, fibroblast cells and certain epithelial cells of the kidney (28).…”
Section: Discussionmentioning
confidence: 99%
“…The invasion and metastases of malignant tumors are complicated biological phenomena, in which cell adhesion serves a vital role (8). VCAM-1 was activated by inflammation (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues such as poor cross-species potency, unsuitable physicochemical properties, selectivity, and inherent class-based toxicity or off-target activity have proven to be a significant hurdle to drug development. For example, PRX.A, an inhibitor thought to be structurally related to compound 6, exhibited nanomolar potency against the mouse enzyme and was efficacious in a murine model of pulmonary metastasis (Ferjan ci c et al, 2013); however, this molecule also had undesirable off-target activity against human dopamine transporter and Na 1 channel proteins at 1 mM. In addition, PXS-4681A, an Improved SSAO Inhibitor with In Vivo Activity Inoue et al (2013a,b,c) documented the development of compound 7, which showed efficacy in a rat streptozotocin-induced ocular permeability model but suffered from poor pharmacodynamic coverage (see below).…”
Section: Discussionmentioning
confidence: 99%